Entrepreneurial Innovation: the European Union perspective - Augustin Ignatov (Review of Economic Perspectives, 2018)
Entrepreneurship is the driving force of economic development and progress. A successful state, first of all, provides favourable conditions motivating the businesses to grow and flourish. Presently, the European Union is developing unevenly with multiple economic misbalances across the community, the West and the North being more competitive than the South and the East. The aim of the present research is to examine the framework of interdependence between the degree to which the governance quality and economic freedom in the European Union are supporting entrepreneurial activities and the performance of the community in terms of entrepreneurial innovation. The results reached through applying both qualitative and quantitative analyses show that the interdependence between entrepreneurial innovation and regulatory efficiency is strong for many of the European Union states which is determined by multiple factors including the institutional and economic ones. Also, the present paper underlines the importance of the proper regulatory framework for the efficient development of business innovation. The future research on this matter could consider in depth the impact of socio-cultural environment, its influence on the quality of governance and the impact of both upon the European entrepreneurial innovation.
Keywords: 330; economic freedom; entrepreneurship; European Union; innovation investments; market behaviour; venture capital